Racial/Cultural Awareness Workshops and Post-College Civic Engagement: A Propensity Score Matching Approach. (December 2016) - Bowman, Nicholas A.; Denson, Nida; Park, Julie J.
Racial/cultural awareness workshops constitute a salient form of co-curricular diversity engagement in higher education. Although these workshops are generally quite short in duration (often no more than two hours), previous research suggests that workshop participation is associated with undergraduate civic growth. The current study uses multilevel propensity score matching analyses to explore whether racial/cultural awareness workshops during college are associated with a variety of civic outcomes six years after graduation. Using a 10-year longitudinal sample of 8, 634 alumni from 229 institutions, diversity workshop participation is significantly and positively related to 10 post-college behaviors, attitudes/beliefs, and skills/tendencies. Moreover, these effects are consistent regardless of participants' race/ethnicity, gender, and institutional affiliation.